Exploring Tetrahydroquinoline Derivatives: A New Frontier in Cancer Treatment - Shaw, Suman K.; Dey, Rajdeep; Yadav, Ruchi; Baldiwala, Aliasgar; Patel, Manan; Patel, Bhumika D.; Bhatt, Hardik G.; Natesan, Gopal; Jha, Abhishek; Chaube, Udit (Synlett, 2025)
Tetrahydroquinoline derivatives are emerging as promising anticancer agents due to their versatile biological activities. In this study, we designed, synthesized, and evaluated six novel tetrahydroquinoline derivatives with anticancer potential. The compounds were synthesized by nitration, benzoylation, and reduction, achieving high yields and structural diversity. Molecular-docking studies on the mTOR protein (PDB ID: 4JT6) revealed strong binding affinities, with key interactions at active-site residues. Molecular dynamics simulations in GROMACS (50 ns) confirmed the stability of the compound–protein complexes. In vitro cytotoxicity assays against A549, MDA-MB-231, and MCF-7 cancer cell lines showed potent activities, with one product displaying an IC50 o
Keywords: anticancer drugs; tetrahydroquinolines; molecular docking